Recoleccion de germoplasma nativo de Phaseolus - Debouck, Daniel G. (1985)
A collection trip of native Phaseolus germplasm was carried out over a 15-day period in the provinces of Jujuy, Salta, Tucuman, and Catamarca (Argentina) within the alt. range of 700-2200 m.a.s.l. Seeds of 26 wild populations of Phaseolus vulgaris var. aborigineus and of other species were collected. P. augusti was found in Tucuman for the 1st time. P. vulgaris populations adapted to both dry and humid environments were found. Several diseases and pests were recorded on populations of this species. (CIAT)